1997
DOI: 10.1152/jn.1997.78.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Dependent Modulation of Spike Burst Length in Cat Striate Cortical Cells

Abstract: Burst activity, defined by groups of two or more spikes with intervals of < or = 8 ms, was analyzed in responses to drifting sinewave gratings elicited from striate cortical neurons in anesthetized cats. Bursting varied broadly across a population of 507 simple and complex cells. Half of this population had > or = 42% of their spikes contained in bursts. The fraction of spikes in bursts did not vary as a function of average firing rate and was stationary over time. Peaks in the interspike interval histograms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 60 publications
2
44
0
Order By: Relevance
“…Indeed, a previous modeling study using a minimal model of a Hippocampal pyramidal neuron has shown burst duration coding in the form of a positive correlation between stimulus slope and burst length (Kepecs et al 2002). This is consistent with experimental results showing correlations between the burst length and stimulus attributes such as orientation (DeBusk et al 1997;Martinez-Conde et al 2002), velocity (Arganda et al 2007, luminance (Gaudry and Reinagel 2008), and sound (Eyherabide et al 2008;Marsat and Pollack 2010). While our modeling results and in vitro data also show a positive correlation between stimulus slope and burst length for ELL pyramidal neurons, our results suggest that the weak correlation between burst length and stimulus amplitude can be accounted by the high variability displayed by ELL neurons in vivo.…”
Section: Burst Dynamics and Codingsupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, a previous modeling study using a minimal model of a Hippocampal pyramidal neuron has shown burst duration coding in the form of a positive correlation between stimulus slope and burst length (Kepecs et al 2002). This is consistent with experimental results showing correlations between the burst length and stimulus attributes such as orientation (DeBusk et al 1997;Martinez-Conde et al 2002), velocity (Arganda et al 2007, luminance (Gaudry and Reinagel 2008), and sound (Eyherabide et al 2008;Marsat and Pollack 2010). While our modeling results and in vitro data also show a positive correlation between stimulus slope and burst length for ELL pyramidal neurons, our results suggest that the weak correlation between burst length and stimulus amplitude can be accounted by the high variability displayed by ELL neurons in vivo.…”
Section: Burst Dynamics and Codingsupporting
confidence: 86%
“…the temporal ordering of spikes within a burst or the number of spikes within a burst) and stimulus attributes (e.g. its amplitude of its rate of rise before burst onset), thereby suggesting that the detailed structure of a burst could provide information about the stimulus (DeBusk et al 1997;Kepecs et al 2002;Martinez-Conde et al 2002;Oswald et al 2007;Eyherabide et al 2008;Gaudry and Reinagel 2008;Marsat and Pollack 2010;Samengo and Montemurro 2010). Studies conducted in simple systems with well-characterized anatomy and relatively simple behaviors are likely to yield significant insight into the functional role of burst firing.…”
Section: Introductionmentioning
confidence: 99%
“…Bursts have been reported to encode sensory information in numerous systems including in olfactory receptor neurons (Eyherabide et al 2008;Rospars et al 2000). In various brain regions, the utility of bursts has been attributed to encoding information by burst duration (Kepecs et al 2002;DeBusk et al 1997;Martinez-Conde et al 2002), number of spikes within the burst (Eyherabide et al 2008), or within-burst ISI (Oswald et al 2007).…”
Section: Vsns Use a "Burst Rate" Code For Representing Sensory Informmentioning
confidence: 99%
“…1 A2,B2), an ISI criterion was established to identify spikes belonging to bursts (Turner et al, 1994(Turner et al, , 1996Debusk et al, 1997;Metzner et al, 1998;Reinagel et al, 1999). A criterion ISI of 10 msec was chosen for in vitro data.…”
Section: Pyramidal Cell Burst Responses To Noise Stimuli Applied In Vmentioning
confidence: 99%